2017
DOI: 10.1038/srep40635
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions and Microbial Communities as Influenced by Dual Cropping of Azolla along with Early Rice

Abstract: Azolla caroliniana Willd. is widely used as a green manure accompanying rice, but its ecological importance remains unclear, except for its ability to fix nitrogen in association with cyanobacteria. To investigate the impacts of Azolla cultivation on methane emissions and environmental variables in paddy fields, we performed this study on the plain of Dongting Lake, China, in 2014. The results showed that the dual cropping of Azolla significantly suppressed the methane emissions from paddies, likely due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 57 publications
(75 reference statements)
6
9
0
1
Order By: Relevance
“…Azolla cover decreased the seasonal CH 4 emission by 34.7% compared to the control treatment without azolla cover (Table 2). This result was consistent with previous recent studies (Bharati et al 2000;Ma et al 2012;Ali et al 2015;Liu et al 2017).The cumulated CH 4 emission from control treatment pot at 55.4 g C m −2 was similar to the value gathered in a field experiments in Yamagata (Itoh et al 2011). Not only azolla, but also common duckweed (Lemna minor), the other floating macrophyte, significantly reduced the mean CH 4 emission from flooded rice paddies in China by 20.4% (Wang et al 2015).…”
Section: Effect Of Azolla Cover On Ch 4 Emissionsupporting
confidence: 81%
See 2 more Smart Citations
“…Azolla cover decreased the seasonal CH 4 emission by 34.7% compared to the control treatment without azolla cover (Table 2). This result was consistent with previous recent studies (Bharati et al 2000;Ma et al 2012;Ali et al 2015;Liu et al 2017).The cumulated CH 4 emission from control treatment pot at 55.4 g C m −2 was similar to the value gathered in a field experiments in Yamagata (Itoh et al 2011). Not only azolla, but also common duckweed (Lemna minor), the other floating macrophyte, significantly reduced the mean CH 4 emission from flooded rice paddies in China by 20.4% (Wang et al 2015).…”
Section: Effect Of Azolla Cover On Ch 4 Emissionsupporting
confidence: 81%
“…5) between control and azolla cover treatments, implying that azolla cover did not affect the CH 4 production in the submerged dual cropping azolla-rice soil ecosystem. This confirmed that the decreased CH 4 emission by azolla cover was due to stimulated CH 4 oxidation (Bharati et al 2000;Ali et al 2015;Liu et al 2017). The sources of CH 4 production are from both older matter (e.g., native soil organic matter, incorporated organic material such as straw and manure , and new matter from plant growth (e.g., root exudates and plant debris).…”
Section: Effect Of Azolla Cover On Ch 4 Emissionsupporting
confidence: 66%
See 1 more Smart Citation
“…As a result of their high growth and N 2 fixation rates, Azolla ferns have been used as a bio‐fertilizer in rice paddies in south‐east Asia for several centuries . Using Azolla as bio‐fertilizer increases the sustainability of rice cultivation by reducing fertilizer requirement as well as reducing nitrogen and greenhouse gas (GHG) emissions from rice paddies . However, a direct use of Azolla biomass for feed production may provide more environmental benefits as well as economic value to farmers, but is not yet common on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the cultivation of Azolla spp. in methane-emanating rice paddies, which are hot spots for methanogenic phenomena, has been shown to alleviate methane emissions in dual cropping systems [27]. The supposed explanation of this observation is that the dissolved oxygen in irrigation systems and the soil redox potential become favorable under Azolla cultivation [27].…”
Section: Methane Emissionsmentioning
confidence: 99%